Closer Insight through Ventriculo-Arterial Coupling Perspective of Late-recognized Peripartum Cardiomyopathy in The Presence of a Predictor of Non-Recovery: Case Report - Mochamad Rizky Hendiperdana (The Indonesian Heart Association, 2026)
Background: Peripartum Cardiomyopathy (PPCM) is ventricular systolic dysfunction that develops in the last months of pregnancy to several months postpartum. Emerging evidence suggests that PPCM may develop up to 1 year after delivery. This condition is associated with several predictors of non-recovery. Case Illustration: A 39-year-old woman was admitted with heart failure syndrome. The patient had late-recognized PPCM after an 18-month postpartum period. Echocardiography showed Left Ventricular (LV) dilation and severely reduced Ejection Fraction (EF). The predictor of non-recovery is also present in this case. However, after 5 months of administered Guideline-Directed Medical Treatment (GDMT), the patient developed structural and complete functional reverse remodeling. During the follow-up period, we observed significant improvement in Left Ventricular Ejection Fraction (LVEF) from 23 % to 57 %, Global Longitudinal Strain (GLS) from –5.2 % to –17.5 %, Left Atrial Strain (LAS)-reservoir from 8 % to 31 %, and global work index (GWI) from 516 mmHg % to 1702 mmHg % from myocardial work index analysis. Conclusions: Several factors have been identified as predictors of non-recovery in PPCM in previous studies, including LVEF <30%, LV dilation, and severe valvular regurgitation. The current scoring system for PPCM recovery, developed by ESC EORP, also predicts 6-month recovery. There was significant improvement in surrogate markers for myocardial systolic function despite of the presence of late-recognized predictors of non-recovery in this case. Hemodynamic phenotype, rather than a single marker measurement, is emerging as a key factor in PPCM prognostication.